CT45A1 siRNA silencing suppresses the proliferation, metastasis and invasion of lung cancer cells by downregulating the ERK/CREB signaling pathway - Tang, Feng (Mol Med Rep, 2017)
The aim of the present study was to investigate the role of the cancer-testis antigen family 45 member A1 (CT45A1) in the proliferation, apoptosis, invasion and metastasis of lung cancer cells, and the associated molecular mechanisms. Western blotting determined that the expression of CT45A1 in normal lung cells was far lower than that observed in lung cancer cells. Following the transfection of CT45A1 small (or short) interfering (si)RNA and its negative control into A549 cells using Lipofectamine 2000, the CT45A1 protein and mRNA levels were determined further by western blotting and reverse transcription-polymerase chain reaction. Following CT45A1 siRNA transfection, the levels of CT45A1 in lung cancer cells were markedly reduced (P<0.01). Then, cell viability and apoptosis were investigated with a methyl thiazolyl tetrazolium assay and Annexin V-FITC/propidium iodide staining, respectively. Transwell assays were employed to evaluate the migration and invasion of A549 cells. When compared with the negative control, the viability, migration and invasion of lung cancer cells treated with CT45A1 siRNA were suppressed and apoptosis was promoted (all P<0.01). In addition, the levels of B-cell lymphoma-2 (Bcl-2), Bcl-2 associated X (Bax), survivin, matrix metalloproteinase 2 (MMP2), MMP9, extracellular signal-regulated kinase 1/2 (ERK1/2), phosphorylated ERK1/2 (p-ERK1/2), cyclic AMP response element binding protein (CREB) and p-CREB were assessed by western blotting. Following CT45A1 silencing, the expressions of Bcl-2, survivin, MMP2, MMP9, p-ERK1/2 and p-CREB were downregulated and the expression of Bax was upregulated (all P<0.01). It was concluded that CT45A1 siRNA silencing suppressed the proliferation, metastasis and invasion of lung cancer cells by downregulating the ERK/CREB signalling pathway.